Qualitative Characteristics of Depression in Parkinson’s Patients and Controls - Cleo Kritzinger; Eva-Juliane Vollstedt; Katja Hückelheim; Anne Lorwin; Julia Graf; Sinem Tunc; Christine Klein; Meike Kasten (Behavioural Neurology)
Background. Depression is common in Parkinson’s disease (PD); in light of typical PD pathology it may differ phenomenologically from depression in the general population. Objective. To assess depressive symptoms in PD patients and control groups and compare symptom profiles. Methods. After postal screening of 10,000 citizens of Lübeck, 642 participants were examined and the Beck Depression Inventory (BDI) was sufficiently answered by 477 subjects. Based on motor examinations, we distinguished PD patients, Healthy Controls (HC, no motor impairment), and Disease Controls (DC, motor impairment other than PD). Results. The sample comprised 331 men and 311 women, aged 65 ± 8 years. Out of the overall sample, 198 (41.5%) had a BDI score ≥9. BDI results above 9 points occurred in 34.5% of HC, 50.3% of DC, and 42.4% of PD patients. Compared to the control groups (HC, DC) the PD patients endorsed more “dissatisfaction” and “loss of appetite” but less “feelings of guilt,” “self-hate,” and “loss of libido.” Conclusion. Depressive symptoms are more frequent in PD patients compared to HC but not DC. Interestingly, the distribution of individual symptoms of the BDI differs between groups with an emphasis on loss of pleasure/enjoyment in the PD group, a symptom typically considered to be dopaminergically transmitted.